Le savant sans le politique : La conception hayékienne de l’action publique au Chili - Damien Larrouqué (Terrains/Théories, 2022)
Chile has always been presented as a laboratory for neoliberalism. In this article, we go beyond this generally accepted consideration. We defend the thesis that it is more a Hayekian model in essence. Based on a reflection of political theory informed by the field, our rationale is divided into two parts. The first shows that the Constitution of 1980 was kneaded by the legal, political and economic doctrine of the Austrian-American intellectual. The third argues how the shadow of Hayekian philosophy has obscured the democratic transition and still emerges empirically in technocratic overvaluation, in mass incarceration as a substitution for the social state, and in a decidedly regressive tax structure.